Combining solar panels with plants for sustainable energy and food production: state of the art - Panda, Sampurna; Kumar, Rakesh; Panda, Babita; Panda, Bhagabat; Raj, Ashish (Institute of Advanced Engineering and Science, 2024)
The need for alternative energy sources becomes extensive because of the escalating cost of fossil fuels. The goal of this paper is to examine the effectiveness of combining photovoltaics and agriculture for better yield. Photovoltaic (PV) solar plants will compete with farms for available land. In this study, the methodologies are discussed how it is possible to maximize land utilization by placing solar arrays and food crops on the same plot of land. The term is proposed